Hyaluronic acid injections for chronic tennis elbow - Gershon Zinger; Alexander Bregman; Ori Safran; Shaul Beyth; Amos Peyser (BMC, 2022)
Abstract Background For most patients, tennis elbow (TE) resolves within 6 months of onset. For those with persistent and painful TE, nonsurgical treatment options are limited. Thousands of studies have tried to find effective treatments for TE but have usually failed. In this study, we tested the hypothesis that injections with hyaluronic acid (HA) would be effective at reducing pain from chronic TE. Methods Patients with a minimum of six months of pain from TE and with a pain level of 50 or greater (out of 100) were included in the study. They were randomized equally into one of two treatment groups: injection with HA or injection with saline control. Follow-up was conducted at 3, 6 and 12 months from the initial injection. Both the patient and the examiner at the follow-up visits were blinded to the treatment arm. The primary outcome measure was the visual analog scale (VAS pain) score at one year. Additional outcome measures included the shortened Disabilities of the Arm, Shoulder and Hand questionnaire (QuickDASH) and Patient Rated Tennis Elbow Evaluation (PRTEE) scores. Results Eighteen patients were randomized into the HA injection treatment arm, and 17 (94%) completed the study. The average age was 51.9 years, and 10 of the subjects were male. Patients had an average of 28.1 months of pain before entering the study. The VAS score in the HA group decreased from a baseline of 76.4-14.3 at 12 months. All 17 patients in the HA group showed VAS score reductions above the minimal clinically important difference (MCID) of at least 18. The PRTEE score improved from 67 to 28.1. The QuickDASH score improved from 53.7 to 22.5. Follow-up in the saline group was less than 50% and was therefore not used as a comparator. Conclusions HA injections yielded significant success in pain relief by three months. Patients continued to improve for the 12-month duration of the study. This study indicates that patients with chronic lateral epicondylitis may benefit from receiving injections of hyaluronic acid rather than having to undergo surgery.